Development Human Resources in Place Cisoka Village Tour Regency Sumedang through Empowerment - Yulianah Yulianah; Chicilia Nova Yatna; Suharyanto Suharyanto (Abdimas Paspama, 2024)
Source Power humans are very important For reach objective . For produce Productive individuals are required good management and development . Development source Power man is form real empowerment . Object tour will develop If source Power the human quality . For example , Tourism Village Cisoka in Sumedang own potency but left behind Because its management less than optimal. Therefore the , Research This aim For explore and analyze empowerment source Power human resources (HR) in place Cisoka Village tourism , Regency Sumedang . Study This use method descriptive with approach qualitative For analyze and explain empowerment source Power humans in objects Cisoka Village tour . Data is collected through observation directly at the Cisoka Village location and interview with parties related like manager and supervisor of Cisoka Village . Research result show that empowerment source Power human resources (HR) in Cisoka Village , Citengah Village , District South Sumedang , via training and practice straight away , have succeed increase capacity public in manage destination tour . previous society not enough realize potency tourism in the village they now more understand and engage active in management tourist . Training management travel and practice field give necessary skills For developing Cisoka Village become destination attractive and sustainable tourism . Evaluation through questionnaire show that training This impact positive , improving knowledge and skills society , as well give contribution significant to development tourist local.